African yearbook of international law = Annuaire africain de droit international. Vol. 23, 2017-2018. - Yusuf, Abdulqawi A. (Leiden : Brill / Martinus Nijhoff, 2018)
Founded in 1993, the 'African Yearbook', now published under the auspices of the African Foundation for International Law, is the only scholarly publication devoted exclusively to the study, development, dissemination and wider appreciation of international law in Africa as a whole. 0Through the study and analysis of emerging legal issues of particular relevance to Africa, such as the creation of viable continental institutions capable of promoting unity and security for the peoples of the continent, the effective protection of human rights, the need for accountability for mass killings and massive violations of the rule of law, the promotion of a rule-based democratic culture, the role of African countries in a globalizing world economy and in international trade relations, the Yearbook strives to be responsive to the intellectual needs of African countries in the area of international law, and to the continuing struggle for creating an environment conducive to the rule of law throughout the continent.
Keywords: International law -- Africa